Living with Paradoxes Victims of Sexual Violence and Their Conduct of Everyday Life - Kappler, Karolin Eva.; SpringerLink (Online service) (Wiesbaden : VS Verlag für Sozialwissenschaften, 2012)
How do women who have survived traumatic sexual violence cope with and manage their everyday lives? Karolin Eva Kappler analyses the everyday life of victims of sexual violence, combining the normalcy of their daily life with the overwhelming experience of rape and sexual abuse. Based on a qualitative study, the author detects five patterns which characterize the victims everyday coping practices and strategies. The grounded analysis of the interview material shows the fragility of the victims lives, depending on paradoxes which reduce their freedom of choice and which explain the individual and social invisibility of sexual violence. The book is valuable reading for academics and practitioners working in the fields of sociology, psychology, medicine, social work, and education.
Keywords: Social sciences; Developmental psychology; Social Sciences; Sociology, general; Gender Studies